Power Quality Analysis of a Grid-connected Solar/Wind/Hydrogen Energy Hybrid Generation System - Sujit Kumar Bhuyan; Prakash Kumar Hota; Bhagabat Panda (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
A grid connected hybrid generation system (HGS) consisting of wind energy conversion System (WECS)/Photo voltaic (PV) System/solid oxide fuel cell (SOFC) is designed and simulated by using Matlab/Simulink. SOFC is the replacement of battery, attached to produce the clean energy when these renewable energy sources are unable to produce required amount of electric power. A controller is used to regulate the flow of H2 through the valveto the SOFC and the rest amount of H2 is stored in storage tank. Also, an operational control strategy (OCS) is developed to utilize maximum amount of power of PV to the required load and rest amount of power is coming from wind to fulfill the load demand. Hence, the electrolyzer is supplied by the wind power to convert the water in to H2 and oxygen. Also the power quality factor (PQF) analysis is exercised to measure the quality of power transmission.